Answer:
x = 1
Step-by-step explanation:
Well the first step is to apply the distributive property:
4(3x - 1) is equal to (12x - 4). You DISTRIBUTE a '4' to what is inside the parentheses.
And btw, to make it easier, you can make 9 - x so that x is first. For example, (-x + 9). They're both the same thing, just written differently.
Your new equation is 12x - 4 = -x + 9. You want to now solve the equation.
Add the (-x) to both sides. It cancels out on the right side and you add it to 12x on the left side.
[If there's no number in front of a variable, you can always just put 1 in order to make it easier]
12x + 1x = 13x. Your new equation is 13x - 4 = 9. This should look very familiar. You simply add 4 to both sides. 9 + 4 = 13
Finally, 13x = 13. Divide 13 ÷ 13 to get 1.
x = 1
Just change the y to all of the answers. The correct answer to this particular one is D. 4
Answer:
x = 20 degree
Step-by-step explanation:
Hope this helps u !!
S = ut + (1/2)a(t²) Subtract ut from both sides
(1/2)a(t²) = S - ut Multiply both sides by 2
a(t²) = 2s - 2ut Divide both sides by t²
a= 2s/t² - 2u/t
a= (2S - 2ut)/t²
Answer is C) but there should be parentheses around the term (2S-2ut)